The health literacy level and eating behaviours of the teachers working at the city center of Eskisehir Turkey - Atay, Emrah; Göktaş, Saniye; Öztürk Emiral, Gülsüm; Dağtekin, Gökçe; Akbulut Zencirci, Sevil; Aygar, Hatice; Arslantaş, Didem; Ünsal, Alaettin (International Journal of Research in Medical Sciences, 2017)
Background: The purpose of this study is to determine the level of Health Literacy of teachers who work at the city center of Eskisehir and to evaluate the relation with eating behaviors and some of possible related variables. Methods: This cross-sectional research study was conducted between 1st of March and 28th of April 2017 with the primary, secondary and high school teachers. Study group consists of 825 teachers who agreed to participate to the study. The Questionnaire form includes the socio-demographic variables of teachers, potential factors associated with the health literacy, Turkish Health Literacy Scale 32 (THLS-32) and The Three-Factor Eating Questionnaire. Results: The mean age was 41.91±8.80 years ranging from 22 to 65 years. The median score of the general index of the THLS-32 was found to be as 32.81 and 52.1% of our study population were found to be above the median score. The participants showed a negative correlation between the scores of ‘emotional eating’,‘uncontrolled eating’ scale and THLS-32, positive correlation between ‘cognitive restraint’ eating scale THLS-32. Conclusions: The health literacy level of teachers is important because of effecting both themselves and students. The teachers and the health care providers should collaborate on the topic more and they should be encouraged to participate in health related programmes.